Nitric Oxide Boosts Bemisia tabaci Performance Through the Suppression of Jasmonic Acid Signaling Pathway in Tobacco Plants - Xu, Yanan; Qu, Cheng; Sun, Xia; Jia, Zhifei; Xue, Ming; Zhao, Haipeng; Zhou, Xuguo (Frontiers in Physiology, 2020)
The intimate relationships between plants and insects start with herbivory, which can be traced back to approximately 420 million year ago. Like many other relationships, plant-insect interaction can be mutualistic, commensalistic, or antagonistic. Within antagonistic relationships, plants deploy inducible defense to insect phytophagy. Insects, however, can evade/suppress effectual plant defenses by manipulating plant defense signaling. Previously, we showed that the sweet potato whitefly, Bemisia tabaci, a global invasive insect pest, can suppress jasmonic acid (JA)-dependent defenses, thereby enhancing their performance on host plants. Given that nitric oxide (NO), a multifunctional signaling molecule, interacts closely with JA signaling pathway, we hypothesized that NO is involved in the suppression of JA defensive responses. Equipped with an integrated approach, we comprehensively examined this overarching hypothesis. We showed that: 1) tobacco plants responded to B. tabaci infestation by accumulating high levels of NO; 2) the exogenous application of SNP, a NO donor, in tobacco plants attracted B. tabaci adults and accelerated nymphal development, plants treated with cPTIO, a NO scavenger, repelled B. tabaci adults, and prolonged nymphal development; and more importantly 3) sliencing of NOA1, a gene associated with NO accumulation, and cPTIO application disrupted the B. tabaci-mediated suppression of JA in plants. Collectively, these results suggest that: 1) NO signaling is activated by B. tabaci infestation, 2) NO is involved in the suppression of JA-dependent plant defense, and consequently 3) NO improves B. tabaci performance on host plants. Our study reflects the remarkable arm race coevolved for millions of years between plants and insects, and offers a potential novel target (nitric oxide) for the long-term sustainable management of this global invasive pest.